Australian Real Estate Management and Development companies and women directors. Issue 1 (15th February 2016) - Dimovski, Bill; Lombardi, Luisa; Ratcliffe, Christopher; Cooper, Barry John
Abstract : Purpose: – There is a large literature advocating the importance of a greater proportion of women directors on boards of publicly listed firms. The purpose of this paper is to examine the numbers and proportions of women directors, including women executive directors, on listed Australian Real Estate Management and Development (REMD) companies to identify how prevalent women directors are on such boards. Design/methodology/approach: – The study examines the numbers and proportions of women directors for 35 REMDs in 2011 and compares this to the broad board composition data on 1, 715 Australian Stock Exchange listed entities. Statistically significant findings are evident due to the identified low proportions. Findings: – The study finds that of all the Financials Sub Industry sector groups, REMDs have the lowest proportion of female directors on theirs boards – eight women on each of 35 company boards compared to 159 men on these 35 boards at 2011. Of the eight, there were only two women executive directors on boards compared to 50 men. Statistically, it appears that having women directors on REMD boards is not considered important. Even at December 2014, there are only ten women on seven company boards and only one remaining executive director of an REMD company. Practical implications: – Given that female board representation is positively related to accounting returns and that there is a growing voice for legislation to impose mandatory proportions of women directors on boards around the world, it may be in the interests of REMD boards to consider appointing more women more quickly. Originality/value: – The study is the first to examine the numbers and proportions of women directors amongst REMD companies to identify the paucity of such women directors.